Advances in accounting behavioral research. Vol. 13 - Arnold, Vicky (Emerald, 2010)
Advances in Accounting Behavioral Research publishes high-quality research encompassing all areas of accounting that incorporates theory from, and contributes knowledge and understanding to applied psychology, sociology, management science, and behavioral economics. Research published in this series encompasses all areas of accounting and covers a broad range of issues that affect the users, preparers and assurers of accounting information. Of particular interest are studies that advance and/or develop theory and studies that address contemporary issues affecting accounting information use and the actors in the surrounding environment. Understanding how accounting information affects each of these actors and their decisions and how accounting re-shapes society are critical. Similarly, the surrounding environment is critical as the social context influences accounting as well as the means for supporting information production and dissemination -- i.e. technology. This volume focuses primarily on this latter aspect and includes studies that examine both the short-term implications of technology use on individuals and the long-term implications of technology on organizational evolution.